The The Impact Of Law No. 6 Of 2023 On Environmental Protection And Management - Yasser Basuwendro; Suhadi; Rofi Wahanisa (Journal of Law, Politic and Humanities, 2025)
The environment is a fundamental right of every citizen, as enshrined in Article 28H of the 1945 Constitution of the Republic of Indonesia. However, the enactment of Law No. 6 of 2023, which ratifies Government Regulation in Lieu of Law (Perppu) No. 2 of 2022 concerning Job Creation, has amended several crucial provisions in Law No. 32 of 2009 on Environmental Protection and Management. This study aims to analyze the impact of these amendments and deletions on environmental governance mechanisms. Using a normative juridical approach and literature-based research, the study qualitatively analyzes changes to key articles. The results show that amendments to Articles 24, 25(c), and 26 narrow public participation in the Environmental Impact Assessment (EIA/AMDAL) process. The deletion of Articles 36, 38, and 40 weakens legal oversight over environmentally impactful businesses/activities. Moreover, the revision of Article 88 undermines the principle of strict liability. These findings indicate policy shift toward accelerating investment at the expense of environmental governance, potentially weakening supervision and law enforcement mechanisms. It is concluded that changes brought by the Job Creation Law create imbalance between economic development and environmental sustainability, while also risking the neglect of the public's right to healthy and safe environment.